PERKEMBANGAN EMOSIONAL ANAK PRA SEKOLAH PENGGUNA GADGET - Nor Isna Tauhidah; Evy Noorhasanah (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2022)
Emotional development is oneof the stages of development that will affectc hildren'sinteractions with other people. Children learn to controltheir emotions whentheyare in arelationship withtheirparents, friends, and theirenvironment. The useof gadgetscanhavevariousimpacts on children, includingchildren's emotions. Thisstudyaims todetermine the emotional developmentofchildrenwhouse gadgets. This research is anobservational research with a non-analyticdescriptiveresearch design. Sampling bypurposive sampling method. The samplesize is 56 respondents. The resultsshowedthat23 respondents (41.1%) whoused gadgets had emotional development as expected and33 respondents (58.9%) withverygood emotional development. The useof gadgetscanhave a positive impact on children'sdevelopmentifdonecorrectly, such as choosingthe right contentthat is able to provideexamplesofgood emotional behavior in childrenand thereshouldalso be controland supervision from parents.